The genus Lanocira Hansen, 1890 (Corallanidae: Isopoda: Crustacea) in tropical Australian waters - Bruce, Niel L.; Sidabalok, Conni (Zootaxa, 2011)
The genus Lanocira Hansen, 1890 is recorded from the southwestern Pacific for the first time. Lanocira grebarree sp. nov. from the Great Barrier Reef is described, and Lanocira gardineri Stebbing, 1904 and Lanocira sp. cf. anasicula Jones, 1982 are recorded from the Great Barrier Reef and Hibernia Reef, in the Timor Sea off Western Australia, respectively. Lanocira grebarree sp. nov. can be identified by the anteriorly rounded, upturned and short rostral process in males in combination with the lack of stiff setae on the dorsal surface of the pleotelson. The similar L. gardineri Stebbing, 1904 is distinguished from L. grebarree sp. nov. by the presence of stiff hyaline setae on the dorsal surface of the pleotelson. A key is provided to the Australian species of Lanocira.